Sejarah Pendidikan Indonesia: Sebuah Refleksi - Subair, Ahmad (PT. Intelek Cendikiawan Nusantara, 2024)
This article discusses various educational problems in Indonesia in the past with a focus on aspects such as limited access to education, social class, gender, geography, unequal quality of education, facilities, teaching staff, curriculum, rigid educational orientation, evaluation-oriented memorization, the relevance of education to the world of work, as well as ethnic and religious discrimination. This research aims to analyze how these factors influence the development of education in Indonesia, as well as their impact on equal distribution of learning opportunities and human resource development. During the colonial period, access to education was limited to certain elites, creating inequality that continued until after independence. Apart from that, a curriculum that is too rigid and irrelevant to the needs of the world of work causes graduates to be unprepared to face market challenges. Ethnic and religious-based discrimination also exacerbates the situation, creating a non-inclusive education system. This article concludes that these problems still leave traces today and require more comprehensive and inclusive policy reform. Reflection on the history of Indonesian education is very important to improve the education system and create fairer opportunities for all of society.